STRATEGI MENINGKATAN KEMAMPUAN MENULIS ARTIKEL DI MASA PANDEMI COVID 19 : STRATEGI MENINGKATAN KEMAMPUAN MENULIS ARTIKEL DI MASA PANDEMI COVID 19 - Lusy Tunik Muharlisiani; Supeno; Siti Azizah (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Writing is an academic culture that must be developed in an educational environment. Along with its development, the distribution of academic work goes beyond geographical boundaries, making it easier for teachers to explore and obtain library study materials. But this convenience is not in line with the teacher's ability to publish his scientific papers. Therefore, the purpose of this paper is to identify ways to improve the literacy of scientific works in reputable publications and report the results of collaboration in increasing the number of publications. The findings show that the weakness of teacher writing is originality, writing is considered a difficult skill, the references cited are not representative and credible, as well as inconsistencies between citations in the text and reference lists, age factors, whereas the resulting scientific work, is necessary in career advancement and knowledge improvement. Based on this fact data, this PKM is aimed at working on the capacity of instructors to compose articl to publish. By strengthening through online discussions and workshops, it is expected that the capacity of instructors who follow the program will increment